Engineering students' needs for listening scaffolding strategies and their perceptions of instructors' performance in an academic listening course. Issue 3 (3rd July 2021) - Taghizadeh, Mahboubeh; Saadatjoo, Saba
ABSTRACT: Background : In many universities, undergraduate engineering students are taught in English rather than their first language. This requires the crucial skill of academic listening, but many students have limited linguistic knowledge and skills, necessitating additional scaffolding by instructors. Purpose : The purpose of this study was thus threefold: (a) to explore the needs of Engineering students for scaffolding in the academic listening, (b) to compare their needs for scaffolding strategies and their performance on the academic listening test, and (c) to investigate the performance of two listening instructors in terms of using scaffolding strategies in their classes. Participants : The participants were 140 undergraduate students of Engineering and two PhD holders teaching academic listening at the Iran University of Science and Technology. Design and Methods : The data for this descriptive, correlational research was collected through a sample of academic IELTS listening test, a questionnaire on scaffolding strategies followed by five open-ended questions, and five sessions of observation of the listening classes. Results : The results showed that in one class with 96% of learners' satisfaction, the most frequently used strategies by the instructor were 'repeating whole or part of a task for the students if needed' and 'waiting for them to answer the questions', while in another class with 30% of the learners' satisfaction, only one strategy, 'providing a comfortable atmosphere for the students to listen to the tasks', received the highest percentage. The results also revealed that 'providing clues and directions to help students find the correct answer' and 'correcting task or the answers of students' were the only two statistically significant strategies required by those who obtained the lowest scores on the academic listening test. Conclusions : The findings revealed that meeting students' needs for scaffolding in listening classes can enhance their satisfaction.